PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI - Nurul Mufaizah Syafithri; Waspodo Tjipto Subroto (Jurnal Education and Development, 2021)
Againts the background of the low economic learning outcomes of students, a Research and Development development research was carried out on web-based learning media using a contextual approach. This research applies the 4D development model, among others, define, design, development, dessiminate. The product test was limited to 20 students using a pretest-posttest control group design which was analyzed with a gain score. The results of the study explained that the learning outcomes in the experimental group had increased with the acquisition of a gain score of 0.6 moderate criteria. While the control group experienced a slight increase in the gain score, it was obtained 0.3 in the moderate criteria. These results prove that web-based learning media is suitable for use as a medium for economic learning.